2016
DOI: 10.1088/1742-5468/2016/05/053207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical symmetries of Markov processes with multiplicative white noise

Abstract: We analyse various properties of stochastic Markov processes with multiplicative white noise. We take a single-variable problem as a simple example, and we later extend the analysis to the LandauLifshitz-Gilbert equation for the stochastic dynamics of a magnetic moment. In particular, we focus on the non-equilibrium transfer of angular momentum to the magnetization from a spin-polarised current of electrons, a technique which is widely used in the context of spintronics to manipulate magnetic moments. We unvei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 75 publications
1
50
1
Order By: Relevance
“…Thus, the symmetry of the Keldysh action under this transformation is a direct proof of the presence of thermodynamic equilibrium conditions. The existence of a symmetry that is related to thermal equilibrium has first been realized in the context of classical stochastic models [197,198,[206][207][208], and these considerations have been extended to the realm of quantum systems in Refs. [189,209].…”
Section: Thermodynamic Equilibrium As a Symmetry Of The Keldysh Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the symmetry of the Keldysh action under this transformation is a direct proof of the presence of thermodynamic equilibrium conditions. The existence of a symmetry that is related to thermal equilibrium has first been realized in the context of classical stochastic models [197,198,[206][207][208], and these considerations have been extended to the realm of quantum systems in Refs. [189,209].…”
Section: Thermodynamic Equilibrium As a Symmetry Of The Keldysh Actionmentioning
confidence: 99%
“…(205), the couplingsū 2,3 can be obtained by taking further derivatives with respect toρ c . However, instead of projecting the flow equation (208) in this way onto equations forū 2,3 , it is more convenient to introduce rescaled quantities as outlined above.…”
Section: Non-equilibrium Frg Flow Equationsmentioning
confidence: 99%
“…In the framework of the Martin-Siggia-Rose-Janssen-deDominicis (MSRJD) path-integral formulation of classical stochastic dynamics [3,4,5], the idea of an equilibrium symmetry of the action was first introduced by Janssen in the late 70s [6,7,8]. Recently, the authors showed that the (zero-source) MSRJD generating functional of equilibrium Langevin processes is invariant under a model-independent discrete field transformation combining time reversal with a thermal translation in the complex plane [9,10,11]. The above-mentioned consequences of this equilibrium symmetry (and its out-of-equilibrium breaking) were derived within this path-integral formalism, and they were generalized with little cost to virtually any type of classical equilibrium dynamics: from simple deterministic Newtonian dynamics, or basic Markov processes, to complex stochastic processes with colored and multiplicative noise.…”
Section: Motivationsmentioning
confidence: 99%
“…The important role of the time discretisation in the Langevin equation is now clearly elucidated [5] and many results have been obtained for the construction of an associated path-integral formalism, whose functional action and Jacobian correctly take into account the choice of discretisation [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although such manipulations are well understood at the Langevin equation level, the situation is less clear for the transformation of fields performed inside the action functional corresponding to the Langevin equation. It is known, for instance, that the use of the stochastic chain rule in the action can yield unsolved inconsistencies, both in statistical field theory [14,7] and in quantum field theory [15,16,17,14,18,19].…”
Section: Introductionmentioning
confidence: 99%